Design of a Wearable Fingertip Haptic Device for Remote Palpation: Characterisation and Interface with a Virtual Environment - Tzemanaki, Antonia; Al, Gorkem Anil; Melhuish, Chris; Dogramadzi, Sanja (Frontiers in Robotics and AI, 2018)
This paper presents the development of a wearable Fingertip Haptic Device (FHD) that can provide cutaneous feedback via a Variable Compliance Platform (VCP). The FHD includes an inertial measurement unit, which tracks the motion of the user’s finger while its haptic functionality relies on two parameters: pressure in the VCP and its linear displacement towards the fingertip. The combination of these two features results in various conditions of the FHD, which emulate the remote object or surface stiffness properties. Such a device can be used in tele-operation, including virtual reality applications, where rendering the level of stiffness of different physical or virtual materials could provide a more realistic haptic perception to the user. The FHD stiffness representation is characterised in terms of resulting pressure and force applied to the fingertip created through the relationship of the two functional parameters – pressure and displacement of the VCP. The FHD was tested in a series of user studies to assess its potential to create a user perception of the object’s variable stiffness. The viability of the FHD as a haptic device has been further confirmed by interfacing the users with a virtual environment. The developed virtual environment task required the users to follow a virtual path, identify objects of different hardness on the path and navigate away from ‘no-go’ zones. The task was performed with and without the use of the variable compliance on the FHD. The results showed improved performance with the presence of the variable compliance provided by the FHD in all assessed categories and particularly in the ability to identify correctly between objects of different hardness.